Mineral nutrition and tolerance to Colletotrichum spp. of Andean blackberry (Rubus glaucus Benth.) in nursery - Bautista-Montealegre, Luis Gabriel; DEantonio-Florido, Leidy Yibeth; Cardona, William Andrés; Bolaños-Benavides, Martha Marina; Fischer, Gerhard (Agronomía Mesoamericana, 2022)
Introduction. Several diseases affect the Andean blackberry cultivation in Colombia, where anthracnose (Colletotrichum spp.) stands out for generating total losses. Objective. To estimate the doses of N, P, K, and Ca that allow greater tolerance to C. gloeosporioides strain 52 in Andean blackberry seedlings. Materials and methods. The experiment was carried out in 2017, in a greenhouse located in Mosquera in the department of Cundinamarca (Colombia), with seedlings sown in a substrate based on a 3: 1 mixture of peat and rice husks. A randomized complete block design with a central composite arrangement of 25 treatments and 15 seedlings were used per experimental unit. The inoculation of plant material was carried out 53 days after had begun the application of the treatments, with mycelial discs at a concentration of 9.53×104 conidia. The severity percentage (Sev), incubation period (IP), disease development rate (r), plant height (PLH), stem diameter (StD), leaf area (LA), chlorophyll content index (CCI), dry weight of the aerial part, and concentration of nutrients were measured. The analysis of variance with Tukey’s test (p<0.05), correlation analysis, generation of response surface models, and principal component analysis with the t-test (p<0.05) was carried out. Results. The severity percentage showed significant differences in the plants that received the fertilization treatments, the allometric variables, and chlorophyll content index were negatively and significantly related with the severity percentage. Simple linear effects models and interaction between elements and four components were obtained, which explained 63 % of the observed variability. Conclusions. The doses of 55, 3, 14, and 9 g plant of N, P2O5, K2O, and CaO, respectively, allowed a higher tolerance of plants against strain 52, as well as higher values in growth variables.